The strength of single crystal copper under uniaxial shock compression at 100 GPa. - Murphy, W; Higginbotham, A; Kimminau, G; Barbrel, B; Bringa, E; Hawreliak, J; Kodama, R; Koenig, M; McBarron, W; Meyers, M; Nagler, B; Ozaki, N; et al. (2010)
In situ x-ray diffraction has been used to measure the shear strain (and thus strength) of single crystal copper shocked to 100 GPa pressures at strain rates over two orders of magnitude higher than those achieved previously. For shocks in the [001] direction there is a significant associated shear strain, while shocks in the [111] direction give negligible shear strain. We infer, using molecular dynamics simulations and VISAR (standing for 'velocity interferometer system for any reflector') measurements, that the strength of the material increases dramatically (to approximately 1 GPa) for these extreme strain rates.